Effects of various packaging systems on the safety and quality of hopiang monggo - Kawanami, Katrina Marie Tanafranca; Villarino, Blanca J. (2010.)
ABSTRACT The study aimed to determine the effects of various packaging systems particularly the use of high barrier films and the application of oxygen absorber on the safety and quality of hopiang monggo. Three packaging systems namely: (1) metallized film (vacuum metallized/cast polypropylene - VMPET/CPP) without oxygen absorbers; (2) high barrier plastic polymer (polyethylene terephthalate/ethylene vinyl alcohol copolymer/ linear low density polyethylene - PET/EVOH/LLDPE) without oxygen absorber and (3) with oxygen absorber, were compared with the current packaging of hopiang monggo which is folded carton box (control). Packed samples were stored at 30°C and monitored for quality deterioration through physico-chemical (moisture content and water activity), microbial and sensory analyses until the samples were deemed unsafe and unfit for consumption. Mold growth dictated the end of shelf life for most of the samples. The control samples has a longer shelf life of 14 d which was significantly (p<0.05) longer than the samples packaged in VMPET/CP without oxygen absorber with shelf life ending after 7 and 8 d of storage, respectively. Likewise, the control sample had significantly (p<0.05) lower moisture content, and water activity compared to the other samples. Consumer acceptance tests showed no significant differences (p>0.05) among the aforementioned samples. On the other hand, hopiang monggo packed in PET/EVOH/LLDPE with oxygen absorber had reached 25 d without mold growth and retained acceptable sensory attribute scores. Moreover, significant (p<0.05) differences were determined between the control samples and samples packed in PET/EVOH/LLDPE with oxygen absorber in terms of moisture content, water activity and sensory attributes. Therefore, the use of oxygen absorbers with a high oxygen barrier film such as PET/EVOH/LLDPE had been effective in inhibiting mold growth without significantly affecting the sensory quality of hopiang monggo.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Food -- Packaging